In-depth investigation of microRNA-mediated cross-kingdom regulation between Asian honey bee and microsporidian - Fan, Xiaoxue; Zhang, Wende; Zhang, Kaiyao; Zhang, Jiaxin; Long, Qi; Wu, Ying; Zhang, Kuihao; Zhu, Leran; Chen, Dafu; Guo, Rui (Frontiers in Microbiology, 2022)
Asian honey bee Apis cerana is the original host for Nosema ceranae, a unicellular fungal parasite that causes bee nosemosis throughout the world. Currently, interaction between A. cerana and N. ceranae is largely unknown. Our group previously prepared A. c. cerana workers’ midguts at 7 days post inoculation (dpi) and 10 dpi with N. ceranae spores as well as corresponding un-inoculated workers’ midguts, followed by cDNA library construction and a combination of RNAs-seq and small RNA-seq. Meanwhile, we previously prepared clean spores of N. ceranae, which were then subjected to cDNA library construction and deep sequencing. Here, based on the gained high-quality transcriptome datasets, N. ceranae differentially expressed mRNAs (DEmiRNAs) targeted by host DEmiRNAs, and A. c. cerana DEmRNAs targeted by microsporidian DEmiRNAs were deeply investigated, with a focus on targets involved in N. ceranae glycolysis/glyconeogenesis as well as virulence factors, and A. c. cerana energy metabolism and immune response. In A. c. cerana worker’s midguts at 7 (10) dpi (days post inoculation), eight (seven) up-regulated and six (two) down-regulated miRNAs were observed to target 97 (44) down-regulated and 60 (15) up-regulated N. ceranae mRNAs, respectively. Additionally, two up-regulated miRNAs (miR-60-y and miR-676-y) in host midgut at 7 dpi could target genes engaged in N. ceranae spore wall protein and glycolysis/gluconeogenesis, indicating potential host miRNA-mediated regulation of microsporidian virulence factor and energy metabolism. Meanwhile, in N. ceranae at 7 (10) dpi, 121 (110) up-regulated and 112 (104) down-regulated miRNAs were found to, respectively, target 343 (247) down-regulated and 138 (110) down-regulated mRNAs in A. c. cerana workers’ midguts. These targets in host were relevant to several crucial cellular and humoral immune pathways, such as phagasome, endocytosis, lysosomes, regulation of autophagy, and Jak–STAT signaling pathway, indicative of the involvement of N. ceranae DEmiRNAs in regulating these cellular and humoral immune pathways. In addition, N. ceranae miR-21-x was up-regulated at 7 dpi and had a target relative to oxidative phosphorylation, suggesting that miR-21-x may be used as a weapon to modulate this pivotal energy metabolism pathway. Furthermore, potential targeting relationships between two pairs of host DEmiRNAs-microsporidian DEmRNAs and two pairs of microsporidian DEmiRNAs-host DEmRNAs were validated using RT-qPCR. Our findings not only lay a foundation for exploring the molecular mechanism underlying cross-kingdom regulation between A. c. cerana workers and N. ceranae, but also offer valuable insights into Asian honey bee-microsporidian interaction.